(untitled) (Research, Society and Development, 2021)
The study aimed to identify and compare the number of coaches and coaches of team sports present in the 31st edition of the Paraná Youth Games (JOJUPs) 2018. A survey was carried out through the official website of the competition promoted by the Department of Sport and Tourism of Paraná. The summaries of all games of the modalities were analyzed: Basketball, Football, Futsal, Handball and Volleyball, male and female, in order to identify whether the coaches were men or women. The results show that out of a total of 740 possible positions for sports coaches, only 12.67% are occupied by women, totaling 96 women, while 87.03% of the positions are occupied by men, which represents 644 men. Among the modalities, both in the male and female categories, the presence of men as coaches is greater, in Basketball, 85% of the 53 teams had men as coaches and only 15% were led by a woman; Of the 190 Futsal teams, 95% were coached by men, while only 5% were coached by women; Soccer, from 128 teams, 96% coaches and only 4% coaches; Handball, of the 50 representations, 80% had male coaches and 20% had coaches; Volleyball, in the 64 teams 84% ​​were male coaches, while 16% were female coaches. At the end of this work, it was possible to verify that the number of women in positions of sports coaches of the collective modalities present in JOJUPs is still very low.